2017
DOI: 10.1055/s-0043-119876
|View full text |Cite
|
Sign up to set email alerts
|

Somatotrope Pituitary Function in Professional Soccer Players

Abstract: In this small collective of soccer players we did not find playing soccer to be a risk factor for the development of GH-deficiency. According to our data screening for somatotrope deficiency is not necessary. Further investigations in larger cohorts are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
2
0
3
Order By: Relevance
“…Nine studies investigated the effects of RSHI on the hormonal response (see Additional file 1: Table S7), with the median sample size of 22 (range 11 to 68) contact sport athletes. One case study reported the acute semi-acute effects of RSHI on hormone levels in a kickboxer [113], and eight studies reported the chronic effects [100,103,104,107,111,[114][115][116]. Five studies that examined the chronic effects of RSHI in boxing and American football revealed growth hormone secretory deficiencies [103,104,114,115], anti-hypothalamus and anti-pituitary antibodies presence [116], insulin-like growth factor 1 [103,114] and adrenocorticotropic hormone [114,115] deficiency, and hypogonadism [104].…”
Section: Hormonal Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Nine studies investigated the effects of RSHI on the hormonal response (see Additional file 1: Table S7), with the median sample size of 22 (range 11 to 68) contact sport athletes. One case study reported the acute semi-acute effects of RSHI on hormone levels in a kickboxer [113], and eight studies reported the chronic effects [100,103,104,107,111,[114][115][116]. Five studies that examined the chronic effects of RSHI in boxing and American football revealed growth hormone secretory deficiencies [103,104,114,115], anti-hypothalamus and anti-pituitary antibodies presence [116], insulin-like growth factor 1 [103,114] and adrenocorticotropic hormone [114,115] deficiency, and hypogonadism [104].…”
Section: Hormonal Studiesmentioning
confidence: 99%
“…Five studies that examined the chronic effects of RSHI in boxing and American football revealed growth hormone secretory deficiencies [103,104,114,115], anti-hypothalamus and anti-pituitary antibodies presence [116], insulin-like growth factor 1 [103,114] and adrenocorticotropic hormone [114,115] deficiency, and hypogonadism [104]. RSHI exposure in soccer players revealed no long-term effects on hormonal responses [100,111]. Overall, sustained exposure to RSHI appears to increase the risk of pituitary dysfunction in contact sport athletes.…”
Section: Hormonal Studiesmentioning
confidence: 99%
“…Bu çalışma elektif laparoskopik TEP ve açık greftli inguinal herni onarımı yapılan yetişkin hasta grubunda yapıldı. Çalışmaya alınma kriterleri olarak; [1] Anestezi muayenesinde Amerikan Anesteziyoloji Derneği skorunun (ASA) 1 ve 2 kategorisinde olması ve [2]. tek taraflı inguinal fıtık olması olarak belirlendi.…”
Section: Gereç Ve Yöntemunclassified
“…tek taraflı inguinal fıtık olması olarak belirlendi. Çalışmadan dışlanma kriterleri [1] nüks veya bilateral inguinal herni olması; [2] inkarsere veya strangüle herni olması; [3] Tartışma Cerrahi travmaya vücudun refleks nöroendokrin yanıtı üç değişik yolla olur; otonom yanıt, hormonal yanıt ve lokal doku yanıtı. Cerrahi travmanın şiddeti ve oluşturduğu inflamasyonun derecesi ile vücutta ortaya çıkan bu cevapların fazlalığı arasında ilişki vardır.…”
Section: Gereç Ve Yöntemunclassified
See 1 more Smart Citation